Advancing pigeonpea variety choices for Kenya’s agricultural future - Kairu, Susan; Mbugua-Gitonga, Agnes; Nadigatla, Ganga Rao; Bett, Charles; Karimi, Rael (CGIAR System Organization, 2025)
Growing of pigeonpea varieties with low production, pest and disease susceptibility, and long maturity periods has significantly contributed to Kenya’s long-term declining production of the crop. To understand the crop’s market opportunities, CIMMYT’s Market Intelligence delved into the following: How adequately represented are the varietal traits crucial toward meeting key grower, industry, and consumer requirements for Kenya’s improved pigeonpea? Qualitative in-depth-interviews (IDIs) were used to deeply analyze local growing, selling, and consumption of pigeonpea. Data were collected from 12 farmers who were also consumers of pigeonpea, an aggregator, KALRO (a seed producer and formal trader), a seed company, and five informal traders. In leveraging thematic saturation, high seed quality emerged as a crucial consideration, represented by creamy grain color, smoothness, oval shape, 6-mm+ size, smooth seed texture, and luster/glossiness. Early maturity, high yield, medium plant height, intercropping compatibility, pod texture, disease resistance, relatively thick stems, ease of uprooting, and high ratoonability were also adoption drivers for farmers. Emerging as important consumer requirements were easy shelling, faster cooking time, adequate grain size before and after cooking, low flatulence, high nutrition, high satiety, as well as low perishability upon harvesting and cooking. Based on the findings, we propose that Kenya pigeonpea Target Product Profile trait categories be grouped into (1) seed quality, (2) crop, (3) agronomic disease, (4) consumer, and (5) processing, with the aforementioned requirements being prioritized. This brief also captures the need for geography-specific improved varieties suited to Kenya’s lowland and relatively highland dry areas, enhanced awareness on improved varieties, and fast-tracking of commercialization of new improved pigeonpea.